Foreign investment, trade, and economic cooperation in the Asian and Pacific region. - United Nations. Economic and Social Commission for Asia and the Pacific (Bangkok Economic and Social Commission for Asia and the Pacific, United Nations, 1992)
Conference papers.
Includes bibliographical references.
Keywords: Investments, Foreign -- Asia -- Congresses; Investments, Foreign -- Pacific Area -- Congresses; Asia -- Economic integration -- Congresses; Pacific Area -- Economic integration -- Congresses